Preparation and Evaluation of the Fully Humanized Monoclonal Antibody GD-mAb Against Respiratory Syncytial Virus - Tian, Puyuan; Wang, Yuqing; Liu, Hui; Yang, Yulu; Wu, Xiaoli; Wei, Hua; Chen, Tingtao (Frontiers in Cellular and Infection Microbiology, 2019)
Respiratory syncytial virus (RSV) is the major cause of pulmonary and bronchial inflammation in infants, young children, and immunocompromised adults, while therapeutic options to control RSV are limited. In the present study, a single chain antibody against RSV (GD-scFv) was screened using phage display library panning technology, and a full-length monoclonal antibody (GD-mAb) was developed based on the sequence encoding Ig VH and Ig VL from GD-scFv. Then, the anti-RSV potential of GD-mAb were evaluated both in vitro and in vivo. Our results indicated that both GD-scFv and GD-mAb possessed a high binding capability and strong binding specificity to GD protein, and plaque reduction neutralization test (PRNT) indicated that GD-mAb could effectively neutralize RSV and reduce plaque number in a concentration-dependent manner in vitro. Moreover, the animal results indicated that GD-mAb had significantly lowered the lung index and reduced the lung virus titer in mice lung (p<0.05), effectively reduced the phosphorylated protein level in pathways of TLR4/NF-κB, MAPKs and PI3K/Akt (p<0.05), which further inhibited the release of pro-inflammatory factors TNF-α, IL-1β and IL-6 in mice lung and serum (p<0.05). These data suggest that the GD-mAb might be used as an effective antiviral agent for RSV infection and treatment.